Sustainable Tourism Versus Massive Tourism: Post-Covid-19 Tourism Industry Driving Scenario - Lastiani Warih Wulandari (International Journal of Artificial Intelligence Research, 2022)
The Covid-19 pandemic situation has made an impact, one of which is for the tourism industry. The impact is not only the responsibility of governments, politicians but also academics and professionals in the field of tourism as a whole in the world. The adaptation of new habits has also been implemented as a solution to revive the tourism industry to be very important. This article shows how the development of Sustainable Tourism can help the continuity of the tourism Â industry, because one of the underlying premises of Sustainable Tourism is that tourism destinations are not too crowded (an important factor in the current context) and not encourage tourism with a lot of tourist visits (masssive tourism) . Considering this argument followed by existing regulations on the adaptation of new habits in the Covid-19 era in the form of implementing health protocols, maintaining distance and social activities by minimizing gatherings, it is considered that this Sustainable Tourism practice Â can be a potential solution to stimulate the movement of tourists and help the revival of the tourism industry. Therefore, more specifically, the main purpose of this article is to find out what travelers' perceptions of Sustainable Tourism are and to determine what factors help its development. The use of scenario models has determined how factors related to tourist attitudes, motivations and perceived benefits provided by the development of Sustainable Tourism can increase tourists' intention to consume this tourism.